μSDN: An SDN-Based Routing Architecture for Wireless Sensor Networks - Santos, Leonardo Francisco da Silva; Mendonça Júnior, Francisco Ferreira de; Dias, Kelvin Lopes (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
Recently, the SDN paradigm, which splits the control and data planes, initially defined for wired networks, has been considered as a solution for the management of WSNs (Wireless Sensor Networks). However, the adoption of OpenFlow protocol, the most widely deployed SDN standard, directly into the WSNs may require novel / customized hardware or incur significant signaling overhead. This paper proposes a novel routing architecture for WSN, based on SDN principles, by extending existing protocols, which allows its deployment in legacy motes. A testbed based evaluation demonstrates the comparable performance results regarding signaling overheads and energy consumption to AODV and LQRP, routing protocols widely used in WSN and extended in this papers as a means of demonstrating the feasibility of a smooth transition to the future all-SDN WSNs. Although a case study has been conducted on a proprietary platform, the paper shows a viable path for similar extensions on other solutions to benefit from flexible management and programmability provided by the SDN paradigm.